«-Ing» supplementive clauses and narrative discourse referents - Martínez, María Ángeles (International Journal of English Studies, 2012)
This study explores the connections between -ing supplementive clauses and narrative discourse foregrounding. Subordinate and, very particularly, non-finite clauses are prototypically associated to narrative background. Using a corpus of extracts from contemporary novels in English, this study, however, shows that this type of subordination displays a predominance of grammatically highlighting features, namely assertive modality, active transitivity processes, and the foregrounded focalizer as most frequent implicit subject. This fact may prove of relevance to both linguistics and literature, as it not only provides a discourse-based cognitive explanation for the apparent incorrecteness of non-co-referential implicit subjects, as in “Leaving the forest, the scent of the trees surrounded them” (Biber et al., 2010: 829), but also suggests that -ing supplementives might intervene in narrative foregrounding, syntactically realizing some of the highlighting devices mentioned in cognitive approaches to the study of language at large (Brisard, 2002; Cristofaro, 2005; Kita, 2008; Talmy, 2000a; Talmy, 2000b), and literary discourse in particular (Tsur, 2009).